Demodex: a skin resident in man and his best friend. (15th May 2020) - Foley, R.; Kelly, P.; Gatault, S.; Powell, F.
Abstract: Demodex mites are microscopic arachnids found in the normal skin of many mammals. In humans, it is well established that Demodex mite density is higher in patients with the skin condition rosacea, and treatment with acaricidal agents is effective in resolving symptoms. However, pathophysiology of rosacea is complex and multifactorial. In dogs, demodicosis is a significant veterinary issue, particularly the generalized form of the disease which can be fatal if untreated. In each species, clinical and molecular studies have shown that the host's immunological interactions with Demodex mites are an important, but not fully understood, aspect of how Demodex can live in the skin either as a harmless commensal organism or as a pathogenic agent. This review outlines the role of Demodex mites in humans and dogs, considering morphology, prevalence, symptoms, diagnosis, histology treatment and pathogenesis.